Review of 'Alzheimer’s Disease, Media Representations and the Politics of Euthanasia: Constructing Risk and Selling Death in an Ageing Society' by Megan-Jane Johnstone - Schweda, Mark (Age, Culture, Humanities: An Interdisciplinary Journal, 2015)
---